CT angiographic patterns of Thai diabetic patients with critical limb ischemia - Srisuwan, Santip; Srisuwan, Tanop; Kaweewan, Rungrujee; Rerkasem, Kittipan (Biomedical Sciences and Clinical Medicine, 2023)
Objectives To define the distribution pattern of peripheral arterial disease (PAD) in diabetic patients with critical limb ischemia (CLI) by using CT angiography. Methods Ninety seven femoral run-off computed tomographic angiographies (CTAs) of diabetic patients with CLI were reviewed retrospectively from March 2010 to January 2013. Vascular obstructive lesions were classified as aortoiliac, femoropopliteal and below knee segments, with details of stenotic severity and lengths. Distribution patterns were analyzed by the Pearson Chi square test. Results There were 478 lesions in 194 limbs. Aortoiliac and femoropopliteal diseases were found more frequently than below knee disease (133 vs. 68) in stenotic lesions less than 10 cm (p= 0.0001) long. However, below knee segment was involved more frequently than above knee disease (121 vs. 30, p = 0.0001) for occlusions equal in length or longer than 10 cm. Conclusions Above knee arterial stenoses are seen frequently as significant in diabetic patients with CLI, and the findings of this study demonstrate both interest in and opportunities for inflow revascularization with endovascular therapy.